Integrated group therapy for bipolar disorder and substance abuse - Weiss, Roger D., 1951; Connery, Hilary Smith (New York : The Guilford Press, 2011)
'Packed with practical clinical tools, this book presents an empirically supported treatment expressly designed for clients with both bipolar disorder and substance use disorders. Integrated group therapy teaches essential recovery behaviors and relapse prevention skills that apply to both illnesses. The volume provides a complete session-by-session overview of the approach, including clear guidelines for setting up and running groups, implementing the cognitive-behavioral treatment techniques, and troubleshooting frequently encountered problems. In a large-size format for easy reference and photocopying, the book features 29 reproducible handouts and forms. Subject Areas/Keywords: addictions, alcoholism, assessments, bipolar disorder, CBT, cognitive-behavioral therapy, co-occurring, counseling, drugs, dual diagnosis, groups, IGT, integrated group therapy, interventions, mood disorders, psychotherapy, relapse prevention, substance abuse, substance use disorders, treatments Audience: Clinical psychologists, social workers, substance abuse counselors, psychiatrists, and other clinicians who treat clients with substance use and mood disorders'--Provided by publisher.
Part 1. Overview Of Integrated Group Therapy -- An Introduction to Integrated Group Therapy -- General Principles of Integrated Group Therapy for Co-Occurring Bipolar Disorder and Substance Abuse -- Therapist Guide for the Integrated Group Therapy Pregroup Interview -- Conducting an Integrated Group Therapy Session -- Part II. Integrated Group Therapy Sessions -- It's Two against One, but You Can Win! -- Identifying and Fighting Triggers -- Dealing with Depression without Abusing Substances -- Dealing with Family Members and Friends -- Denial, Ambivalence, and Acceptance -- Reading Your Signals: Recognizing Early Warning Signs of Trouble -- Refusing Alcohol and Drugs: Thinking It Through and Knowing What to Say -- Using Self-Help Groups -- Taking Medication -- Recovery versus Relapse Thinking: It Matters What You Do -- Taking Care of Yourself -- Taking the Group with You -- Appendix A. Rating Adherence and Fidelity: Ensuring That Integrated Group Therapy Is Done Properly -- Appendix B. Bulletin Board Material -- Appendix C. Frequently Asked Questions about Integrated Group Therapy.
Machine generated contents note: I. Overview of Integrated Group Therapy 1. An Introduction to Integrated Group Therapy 2. General Principles of Integrated Group Therapy for Co-Occurring Bipolar Disorder and Substance Abuse 3. Therapist Guide for the Integrated Group Therapy Pregroup Interview 4. Conducting an Integrated Group Therapy Session II. Integrated Group Therapy Sessions Session 1. It's Two against One, but You Can Win! Session 2. Identifying and Fighting Triggers Session 3. Dealing with Depression without Abusing Substances Session 4. Dealing with Family Members and Friends Session 5. Denial, Ambivalence, and Acceptance Session 6. Reading Your Signals: Recognizing Early Warning Signs of Trouble Session 7. Refusing Alcohol and Drugs: Thinking It Through and Knowing What to Say Session 8. Using Self-Help Groups Session 9. Taking Medication Session 10. Recovery versus Relapse Thinking: It Matters What You Do Session 11. Taking Care of Yourself Session 12. Taking the Group with You Appendix A. Rating Adherence and Fidelity: Ensuring That Integrated Group Therapy Is Done Properly Appendix B. Bulletin Board Material Appendix C. Frequently Asked Questions about Integrated Group Therapy.
Keywords: Bipolar Disorder -- therapy; Psychotherapy, Group -- methods; Substance-Related Disorders -- therapy